Nutritional value and potential uses of amaranth seeds and the outlook to increase the area under the amaranth crop in Poland - Różewicz, Marcin (Polish Journal of Agronomy, 2021)
Amaranthus L. belongs to herbaceous plants with C4- type photosynthesis. The genus Amaranthus contains about 70 species, with three subspecies, including both cultivated and wild types. Amaranth, a pseudo-cereal, has been known to mankind for quite some time and is one of the oldest cultivated plants in the world. It originates from South America, where its cultiva- tion began and where its seeds and green parts were used as food for humans and animals. Nowadays, it is grown in many coun- tries of the Americas, Southeast Asia and Africa. In Europe it is a plant whose cultivation and utilization potential remains under- appreciated. The seeds are gluten-free and contain the valuable health-promoting compound squalene along with tocopherols and carotenoids. As the amaranth seeds have exceptional nutritional qualities, the crop should be cultivated in Europe. Both the seeds and the green parts of amaranth can also be successfully used in animal nutrition. They contribute valuable protein, fat and macro- and microelements to the feed. As evidenced by previous scien- tific research, amaranth can be grown in Poland. It is currently grown on a small scale, but the varied potential uses of the grain offer a good prospect for a significant increase of the area under that crop in Poland. Only two cultivars are currently available for cultivation in Poland so there is much demand fort further breeding work aimed at developing new cultivars adapted to the coutry’s climate. The aim of the study is to discuss the nutritional value and possibilities of cultivation development and use of am- aranth seeds in Poland.